The elements of polymer science and engineering - Rudin, Alfred; Choi, Phillip (Elsevier, 2013)
Suitable for upper or graduate level student studying polymer science and engineering or an engineer new to the field of polymers, this title covers topics such as behavior of natural polymers, polymer nanocomposites, and use of polymers in nanotechnology